Effect of intervention programs in schools to reduce screen time: a meta-analysis - Roberta Roggia Friedrich; Jéssica Pinto Polet; Ilaine Schuch; Mário Bernardes Wagner (Brazilian Society of Pediatrics, 2014)
Objective: to evaluate the effects of intervention program strategies on the time spent on activities such as watching television, playing videogames, and using the computer among school children. Sources: a search for randomized controlled trials available in the literature was performed in the following electronic databases: PubMed, Lilacs, Embase, Scopus, Web of Science, and Cochrane Library using the following Keywords randomized controlled trial, intervention studies, sedentary lifestyle, screen time, and school. A summary measure based on the standardized mean difference was used with a 95% confidence interval. Data synthesis: a total of 1,552 studies were identified, of which 16 were included in the meta-analysis. The interventions in the randomized controlled trials (n = 8,785) showed a significant effect in reducing screen time, with a standardized mean difference (random effect) of: −0.25 (−0.37, −0.13), p < 0.01. Conclusion: interventions have demonstrated the positive effects of the decrease of screentime among schoolchildren.